A DFT study for the structures and electronic spectra of 2,3-dihydropyridine-4-ones - Saeed, Bahjat Ali; Elias, Rita Sabah (European Journal of Chemistry, 2011)
The molecular structure and electronic spectra of eleven dihydropyridones were theoretically studied utilizing density functional (DFT) method. The structures were optimized using B3LYP/6-31G(d,p) level of theory. The conformations of the molecules were analyzed with respect to substituents. The central six-membered dihydropyridone ring adopted a half-chair conformation. The geometries did not differ significantly except for conformations of the phenyl or styryl substituents. The only substituents that affected the structure of the central ring are those which have conjugation overlap with the -C=C-C=O system within the ring. Dipole moments and natural charges were calculated and it was found that in most cases substitution leads to higher dipoles, and both methyl and phenyl substituents have the same effect on the atomic charge distribution leading to decrease the atomic charge on the substitution site. Wiberg bond indices were also calculated and used to analyze the substitution effect on the electronic properties of the molecules. It is concluded that substitution on atoms that are not a part of the N-C=C-C=O system have practically no effect on both structural and electronic properties of the molecules. The electronic spectra were also calculated using the ZINDO method. The predicted spectra are in good agreement with experimental spectra concerning the long wavelength absorption band. The electronic transitions were either pure HOMO to LUMO transitions or comprises components of HOMO to LUMO and other transitions like H-1 to L, H to L+2, H-1 to L+1, H-2 to L+1.